Analysis of Gadget Use at Home on Children's Concentration Aisyiyah Dibal Boyolali Kindergarten - Novitasari, Yosi; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The use of gadgets among children is increasing, including in the home environment, which can affect their ability to concentrate at school. This study aims to identify the causes of Aisyiyah Kindergarten children in Dibal Village using gadgets at home and describe the impact on their concentration at school. Methodology: This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The data was analyzed with a thematic analysis approach in accordance with the Miles and Huberman model, which involved three main stages, namely data reduction, data presentation, and drawing conclusions and verification, namely integrated learning that uses themes to relate several subjects so that they can provide meaningful experiences to students, this is to find patterns in children's behavior related to the use of gadgets and their impact on concentration at school. Results: The results of the study show that the main causes of children using gadgets at home are for entertainment, following the habits of parents, and lack of alternative activities. Excessive use of gadgets leads to a decrease in children's concentration levels while studying at school. Applications/Originality/Value: In conclusion, the use of gadgets at home has a significant negative impact on children's concentration in Aisyiyah Kindergarten, so it is necessary to supervise and time the use of gadgets to minimize these negative impacts.